COVID-19. Return to high performance sport framework (Own the Podium, 2020)
Specifically, in a COVID-19 environment, the resumption of sport can significantly contribute to the re-establishment of normality in Canadian society. Sport organizations and participants will be faced with complex decisions regarding the reopening of training and competition in the current circumstances. The National COVID-19 Return to High Performance Sport Task Force, in consultation with sport partners, Sport Medicine Advisory Committee (SMAC), has developed a COVID-19 Return to High Performance (HP) Sport Framework to inform the resumption of sport. National Principles for Return to HP Sport were used as a guide in the development of the `National Framework`. The National Framework is a tool which consists of a minimum baseline of standards from current evidence, and guidelines from the provincial, territorial, and federal health authorities extrapolated into the sporting context by medical experts in infectious diseases and public health. The National Framework focuses on `ho w` the reintroduction of sport activity will occur in a cautious and methodical manner from an athlete, coach, and practitioner perspective.